The myth of the Marquis de Pombal in fictional narratives - Oliveira, Luiz Eduardo Meneses de; Franco, José Eduardo (Revista Letras Raras, 2023)
<span class="NormalTextRun SpellingErrorV2Themed SCXW12630777 BCX0" data-ccp-parastyle="Normal0" data-ccp-parastyle-defn="{"ObjectId":"15b1f65b-3c3a-4e88-9f53-ee7a0a9f2979|157","ClassId":1073872969,"Properties":[469775450,"Normal0",201340122,"2",134234082,"true",134233614,"true",469778129,"Normal0",335572020,"1",335559740,"276",201341983,"0",469778325,"[\"heading 10\",\"heading 20\",\"heading 30\",\"heading 40\",\"heading 50\",\"heading 60\",\"Title0\",\"Subtitle\",\"footnote text\",\"Normal (Web)\",\"endnote text\",\"annotation text\",\"Balloon Text\",\"header\",\"footer\",\"1 Título em Língua Portuguesa\",\"Título em inglês\",\"4 Parágrafos\",\"5 Citação direta\",\"6 Título de referências - caixa alta sem negrito\",\"7 Lista de referências\",\"caption\",\"Subtitle0\"]"]}">This article is linked to a larger project, entitled Demiurge and Antichrist: the myth of the Marquis of Pombal in literature, whose general objective is to identify, describe and analyze the moments of tension, ambiguity and oscillation of the negative or positive representations of his political economic and cultural action in the literary works that have him as a theme, as well as in those that are set or make reference to his time, during the years of the reign of King José I (1750-1777). In the specific case of this text, we seek to investigate the ways in which the representations of the Marquis of Pombal are mobilized in the novels that have him as a character or protagonist, verifying how such works and/or authors contribute to the process of (de)construction of its mythology, either confirming or contesting the historiographical and biographical narratives about it. In order to do so, we will make use of historiography and documental, legislative and epistolary sources, handwritten or published, as well as some theoretical assumptions related to myths and representations (ELIADE, 2000; BARTHES, 2007; CHARTIER, 2002).